Economic burden due to COVID-19 in a Colombian Caribbean state, 2020 and 2021 - Fernando Salcedo-Mejía; Lina Moyano-Tamara; Josefina Zakzuk; Ana Milena Lozano; Héctor Serrano-Coll; Bertha Gastelbondo; Salim Mattar Velilla; Nelson Rafael Alvis Zakzuk; Nelson J. Alvis-Zakzuk; Nelson Alvis Guzmán (Ministério da Saúde do Brasil, 2024)
Abstract Objective: To estimate the economic burden associated with COVID-19 in Córdoba, Colombia, 2020 and 2021. Methods: Economic burden study. Direct costs were analyzed from the third-party payer perspective using healthcare administrative databases and interviews from a cohort of confirmed COVID-19 cases from Córdoba. Costing aggregation was performed by the bottom-up method. Indirect costs were estimated using the productivity loss approach. Contrast tests and statistical models were estimated at 5% significance. Results: We studied 1,800 COVID-19 cases. The average economic cost of COVID-19 per episode was estimated at US$ 2,519 (95%CI 1,980;3,047). The direct medical cost component accounted for 92.9% of the total; out-of-pocket and indirect costs accounted for 2% and 5.1%, respectively. Conclusion: COVID-19 economic cost was mainly due to direct medical costs. This study provided evidence of the economic burden faced by households due to COVID-19, with the most vulnerable households bearing much of the burden on their income.